Before our eyes : new and selected poems, 1975--2017 - Wilner, Eleanor (Princeton series of contemporary poets., 2019)
A major new collection from the winner of the 2019 Frost Medal for distinguished lifetime achievement in poetryBefore Our Eyes gathers more than thirty new poems by Eleanor Wilner, along with representative selections from her seven previous books, to present a major overview of her distinguished body of work. A poet who engages with history in lyrical language, Wilner creates worlds that reflect on and illuminate the actual one, drawing on the power of communal myth and memory to transform them into agents of change. In these poems, well-known figures step out of old texts to alter their stories and new figures arise out of the local air--a girl with a fury of bees in her hair, homesick statues who step down from their pedestals, a bat cave whose altar bears a judgment on our worship of war, and a frog whose spring wakening invites our own. In the process, ancient myths are naturalized while nature is newly mythologized in the service of life. Before Our Eyes features widely anthologized works such as "Sarah's Choice" and "Reading the Bible Backwards." In the new poems, Wilner records the bewildering public shocks of the current moment, when civic life is under threat, when language itself is attacked, and when poetry's lens of collective imagination becomes a way to resist falsity, to seek meaning, and to really see what is before our eyes